Commonly used herbal remedies for the treatment of Primary Dysmenorrhea and Heavy Menstrual Bleeding by herbalists in Amman, Jordan: A cross-sectional survey - Kattuoa, Mohammad; Issa, Reem; Beitawi, Soha (Jordan Journal of Pharmaceutical Sciences, 2020)
Background: Traditional herbal remedies are commonly prescribed by the local herbalists for female customers complaining of varied health problems. Objectives: The main goal of this study is to assess the perception of herbalists on the use of herbal remedies for the treatment of feminine health disorders; and to prepare two lists of the most commonly used herbal remedies for the treatments of Primary Dysmenorrhea (PD) and Heavy Menstrual Bleeding (HMB). Method: A questionnaire to investigate the beliefs, knowledge and behaviors of a random sample of local herbalists (n=53), on herbal remedies used for the treatment of feminine health disorders was used. Remedies used for the treatments of PD and HMB were reviewed using previously published evidence-based pharmacological studies. Results: Most of the herbalists (68.0%) do frequently get requests for herbal remedies to treat different feminine health disorders. Around two third of the herbalist (66.6%) showed to depend on their work experience as their main source of information on herbal medicine. Of the used herbal remedies, only Zingiber officinale was found clinically effective for the treatment of HMB. While herbalists recommended for 16 herbal species for the treatment of PD, Cinnamomum ceylanicum, Foeniculum vulgare, Trigonella foenum-graecum, and Zingiber officinale proved their benefits in reducing menstrual cycle complications. These treatments were associated with different mechanisms of actions. Conclusion: This study revealed that herbal remedies are commonly used for the treatments of feminine health disorders among the herbalists. Also, these findings shed the light on different herbal treatments that are associated with evidence-based pharmacological studies, for their efficiency and safety in the treatment of PD and HMB symptoms. As such, these treatments would be used as alternatives to the NSAIDs and other hormonal treatments, with not only lower side effects, but also with higher patients' acceptance.